Intangible cultural heritage in industrial design. - Shen, Yu; Cai, Yang-chao; Wang, Xin-yue (Digital Scholarship in the Humanities, 2024)
The research aims to develop an original product design using elements of intangible cultural heritage (ICH). It attempts to evaluate the attractiveness of design with elements of ICH in individual countries and on the world stage. A Master of Art History from Korea National University of Arts participated in the analysis and research of ICH objects. Based on the Gmarket online store, the authors conducted fake door testing to determine the attractiveness of this design for consumers. The method of paired comparisons allowed the authors to assess the attractiveness of a design with the ICH elements on the world stage. Following the project's objectives, the study demonstrated 211 thousand views of the product page with the developed design and 767 thousand views of pages with similar products during one calendar month.